Pengembangan Program Unggulan di SMP Islam Sabilur Rosyad - Muhammad Tareh Aziz; Lestari Widodo (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2023)
The emergence of new Islamic educational institutions has created a new phenomenon in the world of education. That way, of course Madrasas are competing to create new programs that are different from other Madrasas. So quite a few people find it difficult to make choices so that their children can go to good schools and can develop their children's skills. The research method used is qualitative with data collection techniques: observation, interviews and documentation. One of the superior programs that is in great demand in the current era is Islamic boarding schools and tahfidzul Quran. Not a few Madrasas include a superior program in their school curriculum. With this superior program, it will certainly attract a lot of parents of students and even the students themselves to support and develop their skills. One of the schools that uses this superior program is Sabilur Rosyad Islamic Middle School. The curriculum model used at this school is the 2013 curriculum which is integrated with Islamic boarding schools with a full day school learning system. Not a few schools implement the full day school model, but of course this type of curriculum model is very much in demand by modern society, and is very in line with the output of the K13 curriculum, namely by prioritizing character but also not neglecting students' abilities and skills. The superior programs owned by Sabilur Rosyad Islamic Middle School are: Islamic boarding school, Tahsin Al-Quran and Tahfidh Al-Quran, as well as language programs.